ANALISIS KELAYAKAN DAN STRATEGI PENGEMBANGAN USAHA PUPUK KOMPOS MEREK KETAPA DI DESA RANDOTONDA KABUPATEN ENDE - Willybrordus Lanamana; Laurentius Dominicus Gadi Djou; Yohanes Kristono Fowo; Yohanes Pande (Agrica: Journal of Sustainable Dryland Agriculture, 2022)
This study aims to analyze the feasibility of the KETAPA brand compost business, and formulate a development strategy. The research was conducted on farmer groups and livestock groups in Randotonda Village, Ende Regency. Labor involved in production and marketing activities 10 people. This research is a population research. The analysis used is the R/C ratio, B/C ratio, ROI and SWOT. The results of the analysis show that the KETAPA brand compost business is feasible; R/C ratio > 1, the value of B/C ratio, 0.25 means that each production cost is Rp. 100 profits earned Rp. 25. The value of ROI is 26%, the amount of return on investment (ROI) is in the pretty good category. Based on the SWOT analysis, the choice of development strategy is a progressive strategy or SO strategy. Activities include:; building promotion and marketing networks with farmer groups, GAPOKTAN and Field Extension Officers in all districts as well as conducting online marketing